The Unilateral Enigma: An Oral-contraceptive Related Gingival Enlargement - Balaji Anitha; Jennifer W; Mohanasatheesh S; Hema D; Dheeraj S; Menon Nivedha (Journal of Pharmacy and Bioallied Sciences, 2024)
This article’s goal is to describe a case of oral contraceptives-related drug-induced gingival hypertrophy that was treated with nonsurgical and surgical periodontal therapy. The most prevalent negative side effect of systemic medicine on the periodontal tissues continues to be drug-induced gingival overgrowth. Specific regulatory molecules known as hormones control a variety of bodily processes. Gingival hypertrophies are sometimes linked to oral contraceptives that contain oestrogen and/or progesterone. A 32-year-old female presented with a complaint of swelling of the gingiva with spontaneous bleeding in the maxillary right quadrant region for a period of two months. The medical history documented the use of contraceptives for three months, and a clinical examination revealed the existence of poor oral hygiene and enlarged painful gingival tissues that bled when touched. Intraoral examination revealed that there was unilateral, generalized, diffuse gingival enlargement with pseudo pockets. Patient was diagnosed with gingival fibromatosis a based on the clinical, histological, and radiographic findings. The gingival enlargement was treated by conventional gingivectomy under local anaesthesia. The postoperative result was uneventful. Women who use oral contraceptives are a “risk group” for periodontal infections. On oral contraceptives, not every female reacts the same way. In periodontal therapy, plaque management is the most crucial step. Patient compliance is another element that affects a therapy’s response. The patient demonstrated appropriate oral hygiene practices and adhered to home care guidelines adequately.